Analysis of the initial thermal stabilization and air turbulences effects on Laser Tracker measurements. (October 2016) - Pérez Muñoz, Pablo; Albajez García, José Antonio; Santolaria Mazo, Jorge
Highlights: Analysis of the thermal stabilization of Laser Trackers during the first hours of performance and how it affects the measurements. A correction model for the errors caused by internal heating has been developed. Analysis of the effect of air turbulences on measurements with Laser Trackers. Relationship between the turbulences on air and the uncertainty on measurements. Abstract: During the several last years, Laser Trackers have become more common as a measurement tool in the manufacture and assembly of large components such as aircraft wings and ship hulls, as well as for error mapping in coordinate measuring machines and machine tools. Most of these processes cannot be developed in a controlled metrological laboratory but must be implemented directly on a shop floor. Therefore, the process of stabilization of the Laser Tracker has been studied in several experimental tests, and it has been observed that the warm-up time suggested by the manufacturer is not enough. During the first hours of the measurement process two types of thermal errors significantly affect the measurements, causing inaccuracies of between 20 and 80 μm, depending on the equipment used and the positions of the measured points. These thermal errors are systematic and repeatable; therefore they can be estimated and compensated for each measurement system. Because environmental conditions on a shop floor cannot be controlled, once the Laser Tracker is stabilized, the effects of ambient air in measurements have also been studied, focusing on the effect of turbulent flows on the beam path. It has been observed that this turbulence may cause radial distance drifts on the order of micrometers, deflection of the beam trajectory and signal loss.